2020
DOI: 10.1111/cmi.13160
|View full text |Cite
|
Sign up to set email alerts
|

HrpB7 from Xanthomonas campestris pv. vesicatoria is an essential component of the type III secretion system and shares features of HrpO/FliJ/YscO family members

Abstract: The Gram‐negative bacterium Xanthomonas campestris pv. vesicatoria translocates effector proteins via a type III secretion system (T3SS) into eukaryotic cells. The T3SS spans both bacterial membranes and consists of more than 20 proteins, 9 of which are conserved in plant and animal pathogens and constitute the core subunits of the secretion apparatus. T3S in X. campestris pv. vesicatoria also depends on nonconserved proteins with yet unknown function including HrpB7, which contains predicted N‐ and C‐terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 94 publications
(172 reference statements)
0
8
0
Order By: Relevance
“…A similar T3S system‐independent membrane localization was previously described for EscK from E. coli as well as for HrpB7 from X. campestris pv. vesicatoria which is a predicted member of the HrpO/FliJ/YscO family and associates with the IM and predicted C ring components (Drehkopf, Otten, Hausner, Seifert, & Büttner, 2020; Soto et al, 2017). The results of our in vivo and in vitro interaction studies revealed that HrpB4 interacts with the putative C ring protein HrcQ, which is homologous to SctQ proteins from animal‐pathogenic bacteria and might thus be part of the predicted sorting platform of the T3S system (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar T3S system‐independent membrane localization was previously described for EscK from E. coli as well as for HrpB7 from X. campestris pv. vesicatoria which is a predicted member of the HrpO/FliJ/YscO family and associates with the IM and predicted C ring components (Drehkopf, Otten, Hausner, Seifert, & Büttner, 2020; Soto et al, 2017). The results of our in vivo and in vitro interaction studies revealed that HrpB4 interacts with the putative C ring protein HrcQ, which is homologous to SctQ proteins from animal‐pathogenic bacteria and might thus be part of the predicted sorting platform of the T3S system (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that HrcQ interacts with the ATPase HrcN and its predicted regulator HrcL (Lorenz et al, 2012). HrcQ and HrcN both interact with the predicted coiled‐coil protein HrpB7, which is a member of the HrpO/FliJ/YscO family and also binds to the IM ring of the T3S system (Drehkopf et al, 2020) (Figure 9). However, HrpB7 presumably does not act as an essential linker between the sorting platform and the membrane‐spanning secretion apparatus because it is dispensable for the formation of fluorescent HrcQ‐sfGFP foci (Drehkopf et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…targets to the cytoplasmic and/or inner components of T3SS, which presumably is used to regulate secretion and/or translocation of T3SS substrates [11,12,14,22,48,49]. Given that chaperone HpaB may contribute to effector targeting to T3SS, we examined possible interactions of HpaB and its C-terminally truncated variant with secretion platform components of T3SS, such as, HrcN, HrcQ, and HrcU using the GST-pulldown assays.…”
Section: Plos Onementioning
confidence: 99%
“…The T3SS of Xanthomonas is encoded by a chromosomal hrp [hypersensitive response (HR) and pathogenicity] cluster regulated by two master regulators, HrpG and HrpX, whose expression is highly elevated in planta or in particular minimal media [4][5][6][7]. The T3SS of Xanthomonas is a molecular nanomachine and consists of peripheral cytoplasm components (HrcQNL and HrpB7), inner membrane (IM) components (HrcUVRST), periplasm or associated IM components (HrcJ, HrpB1, and HrpB2), outer membrane (OM) component (HrcC), extracellular Hrp pili (HrpE), and translocon (HrpF) [1,[8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%